2014
DOI: 10.4236/ijohns.2014.36065
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Odontogenic Myxoma of the Maxilla: A Case Report and Review of Literature

Abstract: Odontogenic myxomas (OM), also called odontogenic fibromyxomas, are rare tumours of the jawbones. They are benign tumours that can be locally invasive and aggressive, but seldom undergo malignant transformation and do not give rise to metastases. They are often asymptomatic and present as painless swelling. We present herein the case of a 24-year-old patient, with an incidental finding of a maxillary lesion. The lesion expanded to the surrounding soft tissues of the face, the maxillary sinus, the nasal cavity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The patient should be monitored for at least three years after the surgical intervention as the recurrence rate seems to be higher during this period. 1,14,18 The AO reconstruction plate has been used in mandibular reconstruction since the late 1970s. Komisar, et al reported their experience with AO plating for mandibular reconstruction and they were strong proponents of this form of reconstruction because of the ease in applying the prosthesis, the low perioperative morbidityrate, the excellent cosmetic results,and the possibility of rapid rehabilitation of mastication and deglutition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient should be monitored for at least three years after the surgical intervention as the recurrence rate seems to be higher during this period. 1,14,18 The AO reconstruction plate has been used in mandibular reconstruction since the late 1970s. Komisar, et al reported their experience with AO plating for mandibular reconstruction and they were strong proponents of this form of reconstruction because of the ease in applying the prosthesis, the low perioperative morbidityrate, the excellent cosmetic results,and the possibility of rapid rehabilitation of mastication and deglutition.…”
Section: Discussionmentioning
confidence: 99%
“…Myxomas usually occur in the 2nd and 4th decades of life, with a peak in the 3rd decade. [7][8][9][10][11][12][13][14] Radiographically, the tumor presents as a unilocular or multilocular radiolucent lesion with well-defined borders with fine bony trabeculae within its interior structure expressing a "honeycombed", "soap bubble" or "tennis racket" appearance. Unilocular appearance may be seen more commonly in children and in the anterior parts of jaws.…”
Section: Introductionmentioning
confidence: 99%